Enhancing English Speaking Skills Through a Website Used 360-Degree Materials: An Empirical Study - Nasrullah A; Noni, Nurdin; Hakim, Patahuddin; Syawal, Syawal; Akib, Erwin (Lembaga Penelitian dan Pemberdayaan Masyarakat (LITPAM), 2026)
This research examines the influence of 360-degree web-based resources on improving English-speaking proficiency in students, emphasizing their effects on engagement and educational outcomes. Results demonstrate a notable enhancement in speaking abilities, with average scores increasing from 70.5 to 85.7 following the intervention, thereby illustrating the effectiveness of immersive learning environments. The interactive characteristics of 360-degree materials engage students, promote self-directed learning, and cater to various learning styles, while also offering opportunities for practice in real-world contexts. The study highlights the significant role of social interaction enabled by immersive tools, where peer collaboration improves communicative competence through meaningful dialogue and negotiation of meaning. The findings indicate potential; however, the mixed feedback from 35% of students highlights the necessity for continuous evaluation and adjustment of these educational resources to adequately address diverse learner expectations. This study identifies critical deficiencies in comprehending the specific attributes of 360-degree materials that most effectively enhance engagement and learning outcomes among varied student demographics. The website platform that hosts these 360-degree materials is essential to the educational process. It functions as a delivery mechanism for immersive content while also improving interactivity via user-friendly interfaces and accessibility options. This allows students to access materials at any time and from any location, fostering a flexible learning environment that accommodates individual needs. The implications for language education suggest the need for a multifaceted approach that incorporates immersive technologies into curricula, while promoting collaboration among educators, technologists, and curriculum developers to establish dynamic learning environments. Future research should prioritize longitudinal studies to evaluate the long-term impacts of 360-degree materials on language acquisition, examine their integration with other pedagogical strategies, including task-based and experiential learning, and explore effective teacher preparation for the utilisation of these technologies. Focusing on these areas will improve language education and result in more comprehensive educational practices and outcomes.